Keberadaan Teori al-Sarfah dalam Al-Qur'an - Muhammad, Dermawan; Miswar, Andi Miswar; Irham, Muhammad (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2026)
The aim of this research is to review the understanding of Qur'anic miracles through al-ṣarfah theory by solving the problem of stagnation of traditional metaphysical interpretations, while offering the main argument that miracles operate as complex mental phenomena. The approach used is conceptual research with qualitative-descriptive analysis methods and interdisciplinary studies that integrate classical Arabic linguistics with cognitive load theory and modern psycholinguistics. The results showed that al-ṣarfah technically works through three main mechanisms: retrieval disruption with long-term memory access barriers reaching saturation point, erosion of self-efficacy that triggers creative paralysis in the subject, and the phenomenon of cognitive blinding to the deep structure of the text. In conclusion, this study interprets al-ṣarfah not as a physical silencing, but as a logical conclusion of the human brain being aware of its intellectual inferiority, thus providing new value in the dialogue between cognitive science and theology. Future research is suggested to explore specific neurological mapping of how the brain processes the structure of the Qur'anic nazm to empirically validate these findings.